Return to Training and Return to Play Following Soleus-Gastrocnemius Injury - Bisciotti, G. N.; Corsini, A.; Volpi, P. (Return-to-Play after Lower Limb Muscle Injury in Football, 2022)
The soleus muscle and the medial and lateral gastrocnemius muscles compose, with the posterior tibial muscle, the so-called posterior compartment of the leg.